Process of acquisition to destination – a bang on economic prudence with reference to Indian logistics industry - Maran, K.; Usman Mohideen, K. S.; Prabaharan, T.; Senthilnathan, C. R. (University of Jaffna, 2024)
The study explores the significance of the logistics industry in the Indian economy and examines its sector-wise impact on economic well-being. It emphasizes how the presence or absence of transport infrastructure significantly influences economic growth and global competitiveness. With globalization expanding its scope, the study addresses the challenges of global logistics, such as trade laws, cultural differences, and the necessity for efficient cross-border transportation networks. Moreover, the research delves into factors driving the growth of the Indian logistics industry. Innovations and developments are seen as pivotal to economic progress, with intelligent logistics and smart transportation playing crucial roles. The Logistics Performance Index (LPI), a benchmarking tool by the World Bank, ranks countries based on logistics performance. In the 2023 report, India achieved an LPI rating of 3.4, securing the 38th position among 139 countries. The study substantiates the factors fueling the logistics industry with statistical evidence, highlighting technological advancements and the integration of IoT-enabled facilities as key drivers. Furthermore, the study discusses strategic initiatives aimed at enhancing India's logistics infrastructure. The PM Gati Shakti initiative seeks to streamline infrastructure development by promoting integrated planning and coordinated implementation across government departments. Concurrently, the National Logistics Policy (NLP) provides a comprehensive framework for the industry's development. Additionally, the Unified Logistics Interface Platform (ULIP) facilitates real-time information exchange among stakeholders, thereby simplifying logistics planning.
Keywords: Digitalisation; Effect; Indian Logistics Industry; Policies; Prudent Economy